Analogue experiments for the Shuangyushi area in the north western Sichuan Foreland Basin and their implications - Lianjin Zhang; Jiaqiang Huang; Qiang Luo; Yu He; Hao Yu; Rongjun Yang; Xiao Liang; Zheng Zhou; Bin Deng (地质科技通报, 2021)
In this study, we conducted three sets of analouge experiments, i.e., the pilot experiment with homogeneous quartz sand with frontal ramp, scaled experiments with embedded layer of silicone and/or frontal ramp, for the Shuangyushi area in the north western Sichuan Foreland Basin.It suggests that the north western Sichuan Foreland Basin is dominated with two-layer style of deformation, in particular, with pop-up in deep strata which is controlled by the basal decollement and frontal ramp.It should be noted that the frontal ramp has significant influence on the undistributed deformation and related fault-style occurred at the overlying sequences, which are in favor of formation for a pathway system between Lower Cambrian Qiongzhushi Formation and Mesozoic carbonate/dolomite reservoir.In contrast to duplex as a result of multistage deformation in the thrust-and-fold-belt, the north western Sichuan Foreland Basin is characterized with gentle deformation, as a result of forelandward propagation deformation in Cenozoic, and thus with a better quality of hydrocarbon preservation.Analogue experiments have been a powerful and indispensable tool to help us understand the thrust-fold-belt and foreland basin, as well as their hydrocarbon accumulation, from nature to models.